Novel CSR & novel coronavirus: Corporate social responsibility inside the frame of coronavirus pandemic in Greece - Ioannis Panagiotopoulos (International Journal of Corporate Social Responsibility (JCSR), 2021)
Corporate Social Responsibility (CSR) becomes popular as big international firms gain more power than states and global issues engender concerns to people from all over the world. The pandemic of novel coronavirus is a current issue of global concern that threats humanity and global economy since the end of 2019. A lot of firms have announced urgent actions to support their employees and the local communities. The present study aims to examine whether the CSR activities of firms due to the pandemic could be categorized either as strategical or tactical CSR. The researcher recognizes the formation of a new kind of CSR called critical CSR as a hybrid between tactical and strategical CSR sharing characteristics from both. The examination of the case of Greece during the pandemic has provided a variety of examples of CSR activities from big Greek international firms that have been processed to support the validity of the reasoning. Finally, the paper delineates this new universal form of CSR born under the critical circumstances of the pandemic and the ensuing economic recession. That fact proves that this crisis could be transformed into a chance for corporations to realize their social role and improve their CSR footprint with the learnings of this pandemic by underlining possible advantages of these urgent CSR actions that could be incorporated into the usual CSR policy of the firms.
Keywords: 650; Corporate Social Responsibility; Stakeholders; Economic & Health Crisis